2005
DOI: 10.1002/aic.10734
|View full text |Cite
|
Sign up to set email alerts
|

Model prediction of hot spots formation in shallow adiabatic packed‐bed reactors

Abstract: Transversal hot zones have been observed in many industrial and laboratory reactors. Yet, previous models which utilized rate expressions that depended only on the temperature and concentration of the limiting reactant failed to predict formation of stable hot zones. We previously proved that pseudohomogeneous models of a uniformly active shallow adiabatic packed‐bed reactor cannot predict a bifurcation to stable hot zones when the transversal heat dispersion is larger than that of the species, and the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Sheintuch and Nekhamkina [19] analyzed the pattern formation in homogeneous model of a fixed catalytic bed for reactions with oscillatory kinetics. Viswanathan and Luss [20][21][22] ied the conditions for the existence of hot zones in a uniformly active shallow as well as long adiabatic packed bed reactors using a two-phase model. Mathematical models developed to study chemical reactors are derived from balances of species, energy, momentum and continuity in conjunction with various constitutive relationships, and they form a set of unsteady state three-dimensional partial differential equations containing a large set of physiochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Sheintuch and Nekhamkina [19] analyzed the pattern formation in homogeneous model of a fixed catalytic bed for reactions with oscillatory kinetics. Viswanathan and Luss [20][21][22] ied the conditions for the existence of hot zones in a uniformly active shallow as well as long adiabatic packed bed reactors using a two-phase model. Mathematical models developed to study chemical reactors are derived from balances of species, energy, momentum and continuity in conjunction with various constitutive relationships, and they form a set of unsteady state three-dimensional partial differential equations containing a large set of physiochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…first-order reaction) with pseudohomogeneous models or two-phase models with very small inter-phase gradients. Other authors (Viswanathan et al, 2005;Viswanathan and Luss, 2006) have reached a different conclusion and state that there is no qualitative difference between pseudohomogeneous models and two-phase models with respect to pattern formation.…”
Section: Estimation Of the Range Of Parameter Values For Pattern Formmentioning
confidence: 91%
“…Marwaha et al (2004) and Sundarram et al (2005) have shown that global coupling can lead to formation of hot zones on the top of a packed-bed reactor. Recently, Viswanathan et al (2005) and Viswanathan and Luss (2006) showed that a stable stationary hot zone can form in the cross-section of a packed-bed reactor only under the unrealistic assumption that the transversal species dispersion exceeded that of the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…40 ] This approach has been demonstrated successfully for models of reactor operated under adiabatic conditions. [27][28][29]41 We extend this to nonadiabatic reactor model. The pseudo-homogeneous model of the shallow, non-adiabatic packed-bed reactor (SNAR) is (12) with the corresponding boundary conditions being…”
Section: ■ Calculations and Modelingmentioning
confidence: 98%